A BOOK REVIEW ARTICLE: THE BEAUTY MYTH: HOW IMAGES OF BEAUTY ARE USED AGAINST WOMEN - Ekawati Marhaenny Dukut (Soegijapranata Catholic University, 2005)
NAOMI WOLF New York: Perennial, 2002, 348pp, ISBN 0-06-051218-0